Messages of Ecological Awareness in the Pa’a Loka Ritual of Water Sources among the Lio Indigenous People, Ende Regency, Flores: Pesan Kesadaran Ekologis Dalam Ritus Pa’a Loka Sumber Air Dalam Masyarakat Adat Lio Kabupaten Ende Flores - Kusi, Josef; Helena Mau (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The formulation of the problem in this study is; 1). What is the process or stages of the traditional rite of pa'a loka in the water source in the Lio Ende indigenous community, 2), What is the message of ecological awareness in the ritual of pa'a loka in the water source in the indigenous people of Lio Ende. 3). What is the ecological and anthropological view in the rite of pa'a loka water source in the indigenous people of Lio Ende.The purpose of this study is to; 1). Knowing the process of pa; a loka at water sources in the indigenous people of Lio Ende, 2). Knowing the message of ecological awareness in the ritual of pa'a loka at the water source in the indigenous people of Lio Ende. The rite of the water source in the Lio Ende community.3). To know the ecological and anthropological views of the ritual of the water source in the Lio Ende community. The method used in this study is qualitative descriptive. The data collection techniques are observation, interviews and documentation. The data analysis techniques in this study are; 1) data collection, 2) data reduction, 3) data presentation. 4) Draw conclusions. The results of the study show that the process or stages in the rite of pa'a loka water source in the indigenous people of Lio Ende go through three stages, namely; preparation, implementation and final. The message for the younger generation is that traditional rituals continue to be carried out, protecting the forest by, not illegally logging, so that the water discharge remains stable. Through the ritual of the Lio Ende indigenous people, ask for the blessing of the ancestors and provide abundant water. The ecological view in the ritual pa'a loka at the water source is to maintain a harmonious balance of relations between the environment, nature and humans. Anthropological views; Perpetuate the endless relationship between the surviving generations and the ancestors